Cattle breed preferences and breeding practices in southern Nigeria - Swallow, B.M.; Jabbar, M.A. (International Laboratory for Research on Animal Diseases, 1994)
Reports on completed and planned research to examine farmers' perceptions of different breeds, the discretion they exercise over breed composition, and the impacts of breed perceptions on breeding practices. ILCA has recently undertaken three household surveys that shed light on farmers' breed preferences and breeding practices. The survey results indicate that farmers' breed prortfolios are the outcome of dynamic processes that vary across farmers and environmental conditions. A 1986/87 survey of 66 cattle owners indicates that the percentage of zebu in the herds of settled Fulani agro-pastoralists decreases with the length of settlement, while a 1990 survey of 56 cattle owners shows that breeding practices vary greatly across farmers within particular areas. A 1989 survey of 50 cattle owners with zebu and N'Dama cattle indicates that farmers breed preferences are shoped by their perceptions of a variety of characteristics. Summarizes the method and some of the results from those surveys. The results support several proportions regarding breed preferences and breeding practices that will be pursued in research now being initiated. A summary of the methods to be used in that research will be presented.